Polyphenoloxidase activity of minimally processed "Jonagored" apples (Malus domestica) - Rocha, A. M. C. N. (2011)
The influence of three chemical dips using ascorbic acid (AA), citric acid (CA) and calcium chloride (CC) on the polyphenoloxidase (PPO) activity and on the total phenolic content of minimally processed (MP) apple (Malus domestica, cv. Jonagored) during cold storage was evaluated and a potential relationship with enzymatic browning was investigated. An ascorbic acid dip (42.6 mM) of 5 min duration was the most efficient chemical treatment in reducing the PPO activity of apple cubes. A 92% inhibition was achieved after 7 days of storage at 4C. All treatments were advantageous in comparison to the control in reducing color changes. Color changes, determined by absorbance at 420 nm (soluble pigments) and lightness (L) (insoluble pigments) of apple cubes treated with ascorbic acid were correlated with total phenolic content. No correlation was observed between PPO activity and tristimulus color parameters, browning index or total phenolic content of AA-treated apple cubes.